Information exchange in virtual communities: a typology - Jean Gladwin; R.A. Dixon; T.D. Wilson (Information Research: An International Electronic Journal)
Reports on an ethnographic case study of the evaluation of PHC-MAP (a set of information management tools) in an East African country. The attempt at innovation is considered within the framework of Rogers's diffusion of innovation theory and Leavitt's theory of dynamic equilibrium in organizations.